Managing lower extremity loading in distance running by altering sagittal plane trunk leaning - Braun, L.; Mai, P.; Hipper, M.; Denis, Y.; Helwig, J.; Anedda, B.; Utku, B.; Gehring, D.; Willwacher, S. (Journal of Sport and Health Science, 2025)
Background Trunk lean angle is an underrepresented biomechanical variable for modulating and redistributing lower extremity joint loading and potentially reducing the risk of running-related overuse injuries. The purpose of this study was to systematically alter the trunk lean angle in distance running using an auditory real-time feedback approach and to derive dose-response relationships between sagittal plane trunk lean angle and lower extremity (cumulative) joint loading to guide overuse load management in clinical practice. Methods Thirty recreational runners (15 males and 15 females) ran at a constant speed of 2.5 m/s at 5 systematically varied trunk lean conditions on a force-instrumented treadmill while kinematic and kinetic data were captured. Results A change in trunk lean angle from -2° (extension) to 28° (flexion) resulted in a systematic increase in stance phase angular impulse, cumulative impulse, and peak moment at the hip joint in the sagittal and transversal plane. In contrast, a systematic decrease in these parameters at the knee joint in the sagittal plane and the hip joint in the frontal plane was found (p < 0.001). Linear fitting revealed that with every degree of anterior trunk leaning, the cumulative hip joint extension loading increases by 3.26 Nm·s/kg/1000 m, while simultaneously decreasing knee joint extension loading by 1.08 Nm·s/kg/1000 m. Conclusion Trunk leaning can reduce knee joint loading and hip joint abduction loading, at the cost of hip joint loading in the sagittal and transversal planes during distance running. Modulating lower extremity joint loading by altering trunk lean angle is an effective strategy to redistribute joint load between/within the knee and hip joints. When implementing anterior trunk leaning in clinical practice, the increased demands on the hip musculature, dynamic stability, and the potential trade-off with running economy should be considered.